A novel approach in using insect-based spinach-food waste for gene targeting to cancer tissues - Shadi Majd-Marani; Ali Eftekhari; Sabry G. Elias; Roland Beffa; Mohammad Taghi Alebrahim; Abhay Prakash Mishra; Mehdi Afrouz (Scientific Reports)
Abstract In our study, we prepared Fe3O4 nanoparticles (NPs) using food waste extract of Mealworm (Tenebrio molitor) larvae fed spinach (Spinacia oleracea), which is rich in iron. A coating was applied to Fe3O4 NPs containing hyperbranched spermine-polyethylene glycol-folic acid (FHSPF) and spermine-polyethylene glycol-folic acid (FSMPF). Polymer was loaded with siRNA or DNA. DLS1, H-NMR, FTIR, EDX, Zeta potential and TEM were used to analyze morphology of NPs. Biocompatibility, DNA release, and gene transfer properties were evaluated. Coats concentration in our NPs increased zeta potential, DNA release, encapsulation, and gene delivery efficiency. As determined by cell viability, our NPs exhibit low cytotoxicity and good compatibility; on the other hand, we evaluated their ability to transfer into MCF-7 cells using fluorescence microscopy and flow cytometry. According to this analysis, increasing DNA or siRNA concentration in NPs improved gene transfer efficiency. As a result of cytotoxicity assay, FHSPF2 NPs showed high biocompatibility; NPs were demonstrated to deliver siRNA-FAM to breast cancer cells and mice in vivo, and they were also rated excellent for delivering siRNA-FAM to the tumor site using external magnetic fields. Magnetic fields significantly cause NPs to adsorb at the tumor site.